Optimizing Municipal Solid Waste (MSW) Collection and Transportation Network Using GIS and Agent-based Modeling Approach: A Case Study in Hung Yen City, Vietnam - An, Ngo The; Bang, Tran Nguyen; Lan, Nguyen Tuyet; Viet, Nguyen Quoc; Trung, Nguyen Duy (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 3, 2024)
This paper presents a method for optimizing the municipal solid waste (MSW) collection system using a simulation model that integrates spatial analysis and an agent-based modeling approach. Parameters for the model, including waste generation loads, collection points, and collection rates, were obtained through field surveys in Hung Yen city. Optimization scenarios were formulated based on the environmental management goals of the local authorities, which include a population growth rate of 1.5%, the expansion of collection routes (adding two new “hand-pulled garbage” routes), additional vehicle investment (two garbage compactors and 40 hand carts), and at-source treatment (more than 25% of households). The scenario analysis shows that all tested factors effectively reduce MSW generation and residue by 59% compared to the “business as usual” scenario. The optimal routing under the formulated scenarios requires establishing 10 additional transfer points and routes through densely populated areas to achieve the local authorities' goal of a collection rate over 80%. Despite these interventions, some households remain outside the collection service. This finding suggests that additional solutions, such as waste recycling for households not covered by the MSW collection service, are necessary to achieve the sustainable development goals for the locality.